2023
DOI: 10.3233/adr-230060
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Mild Cognitive Impairment in Middle-Aged and Older Chinese People: A Cross-Sectional Study

Qing Xiao,
Yonggang Li,
Benchao Li
et al.

Abstract: Background: The evidence concerning dietary diversity and cognitive function remains insufficient. Objective: To investigate the association of dietary diversity score (DDS) with mild cognitive impairment (MCI) and cognitive performance in different domains. Methods: Data from The Lifestyle and Healthy Aging of Chinese Square Dancer Study was used in this study. DDS was constructed based on the intake frequencies of 9 food groups assessed by a validated food frequency questionnaire. MCI was diagnosed by Peters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Among the individual lifestyle behaviors, we found that healthy diet showed stronger interaction with cognitive function on mortality risk than other lifestyle behaviors. The finding was supported by previous studies that good dietary diversity was associated with a reduced risk of cognitive impairment among elderly people [31,[44][45][46]. Even though the biological mechanism underlying the interaction was not clear, several plausible explanations have been proposed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Among the individual lifestyle behaviors, we found that healthy diet showed stronger interaction with cognitive function on mortality risk than other lifestyle behaviors. The finding was supported by previous studies that good dietary diversity was associated with a reduced risk of cognitive impairment among elderly people [31,[44][45][46]. Even though the biological mechanism underlying the interaction was not clear, several plausible explanations have been proposed.…”
Section: Discussionsupporting
confidence: 79%
“…Even though the biological mechanism underlying the interaction was not clear, several plausible explanations have been proposed. First, good dietary diversity has been reported as a proxy indicator of nutrient adequacy [46] that can help reduce the burden of cognitive impairment [47,48]. Second, low dietary diversity is associated with enhanced oxidative stress, which would affect normal brain function and increase the risk of mild cognitive impairment [49,50].…”
Section: Discussionmentioning
confidence: 99%